What to do with the brine? a zero-discharge solution from CLLEEN Water and Power - Migyanka, Anthony (Knovel, 2012)
"Wastewater treatment for shale gas drilling has evolved rapidly in recent years. With growing demand not only for freshwater itself for fracturing but also for additives to the water for proper well formation, combined with the added pressure of dwindling hazardous disposal options for flowback water, recycling and reuse of the water is making the economic journey to its logical conclusion of producing no waste whatsoever, resulting in zero solids discharge, zero liquids discharge, and 100 percent recycle and reuse."
Knovel brief article.
At head of title: Cases.
Keywords: Shale gas industry -- Waste disposal.; Hydraulic fracturing -- Waste disposal.; Recycling (Waste, etc.); elektronické knihy; electronic books